The intertemporal guarantee of freedom – a concept for international human rights to address states’ failure to combat climate change and its threats? - Gegenwart, Matthias (Vilnius University Open Series, 2023)
This paper analyses, if the Intertemporal Guarantee of Freedom, that was developed by the German Federal Constitutional Court (GFCC), can be used to expand the protection of human rights against the harms of climate change. The case of the Swiss Senior Women shows that there are jurisdictions, where the Intertemporal Guarantee of Freedom could be applied to improve standing and the control standard of states’ climate change action. Within international law bodies with jurisdiction over human rights treaties there are distinctive standards of protection against the harms of climate change. A major deficit within the international human rights protection against climate change lies within the focus on the positive obligations and the corresponding wide margin of appreciation granted to the states. The Intertemporal Guarantee of Freedom could provide a protection expansion in this regard, especially in the case of the European Court of Human Rights. It could also enable and legitimise present human rights concerns focused on the future actions of states following their past inaction. One considerable hurdle that is not addressed by it are procedural hurdles like the Plaumann formula applied by the European Court of Justice. The Intertemporal Guarantee of Freedom cannot solve major problems for climate change litigation like procedural hurdles. Yet, it can provide a new approach for complaints to address unambitious mitigation legislation which will lead to future human rights infringements.